The Colour of Lustre: Limning by the Life - Anne-Valérie DULAC (E-REA)
The present article explores the polysemy of “lustre” in two treatises on limning by Nicholas Hilliard and Edward Norgate. It first lists all uses of the word in these texts in order to offer historically specific definitions of “lustre” in both the practice and theory developed by these specialists of portrait miniatures. This preliminary investigation concludes on the essential although non-intrinsic link between colour and lustre, which finally leads to the study of the mimetic import of a word taken alternately or simultaneously as a technique and a concept.